Fighting Populism on Its Own Turf: Experimental Evidence - Vincenzo Galasso; Massimo Morelli; Tommaso Nannicini; Piero Stanig (Center for Economic Studies and ifo Institute (CESifo), 2022)
We evaluate how traditional parties may respond to populist parties on issues that are particularly fitting for populist messages. The testing ground is the 2020 Italian referendum on the reduction of members of Parliament. We implement a large-scale field experiment, with almost one million impressions of programmatic advertising, and a survey experiment. Our treatments are an informative video on the likely costs of cutting MPs, aimed at deconstructing the populist narrative, and a reducing trust video aimed at attacking the credibility of populist politicians. Our field experiment shows that the latter video is more effective at capturing the viewers' attention. It decreases the turnout rate and, albeit less, the "Yes" votes (in favor of cutting MPs). We present a theoretical framework based on trust in traditional parties and information acquisition to account for our findings and provide additional predictions. In the survey experiment, both (unskippable) videos reduce the "Yes" votes and increase the share of undecided. Confirming the theory, for voters of traditional parties the effects are concentrated among people with low information, while for voters of populist parties previous information plays no role. Our findings show that campaign messages should target not only demographic characteristics but also trust attitudes.
Keywords: D72; C93; 330; field experiment; programmatic advertisement; electoral campaign